Solve for y 6=2(y+2)

Math
6=2(y+2)
Rewrite the equation as 2(y+2)=6.
2(y+2)=6
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2(y+2)=6 by 2.
2(y+2)2=62
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2(y+2)2=62
Divide y+2 by 1.
y+2=62
y+2=62
Divide 6 by 2.
y+2=3
y+2=3
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 2 from both sides of the equation.
y=3-2
Subtract 2 from 3.
y=1
y=1
Solve for y 6=2(y+2)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top